Immigration Policy in Integrated National Economies - Thomas K. Bauer; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2000)
Migration is an unavoidable aspect of globalization. While full flexibility is politically unfeasible, the paper argues for regulated openness. Migration in the age of globalization should be judged according to the labor market needs of the receiving countries. This would also serve best the demands of political leaders that seek reelection. Voters are happier with migrants if they are largely selected according to their value to the economy. In the current situation in developed countries it is best to select skilled migrants, and those who can produce non-tradable services. The need to import skilled labor might be limited by virtual migration through the Internet.
Keywords: J61; J68; 330; Migration policy; globalization; Migrationspolitik; Qualifikation; Humankapital; Hochqualifizierte Arbeitskräfte; Globalisierung; Public Choice; Deutschland